Gigerenzer the Decided: A Tale of Difficult Distinctions - Floris Heukelom (Tinbergen Institute, 2005)
This paper provides an overview of the work of Gigerenzer, thereby focusing on his criticisms of the Heuristics and Biases theory of Kahneman and Tversky. It is proposed that Gigerenzer's work can be both thematically and chronologically organized as: historical research on statistics => criticism on Kahneman and Tversky => the bounded rationality research program. That is, Gigerenzer' attacks on the Heuristics and Biases program derive from his historical work on Brunswik and Thurstone. In turn, these attacks functioned as the driving force behind the development of the bounded rationality research program. Behind the debate, it is argued, lies a fundamental different idea of how human decision-making is to be understood and investigated.
Keywords: B00; B20; B31; 330; Gigerenzer; Kahneman and Tversky; Cognitive Psychology; Bounded rationality; decision-making